Association between N, N-diethyl-m-toluamide exposure and the odds of kidney stones in US adults: a population-based study - Wei, Chengcheng; He, Jiatai; Wei, Zhuo; Huang, Yu; Xiong, Ming; Deng, Changqi; Chen, Zhaohui; Li, Wencheng; Zhang, Xiaoping (Frontiers in Public Health, 2023)
Background: Currently, there is limited research on the specific relationship between N, N-diethyl-mtoluamide (DEET) exposure and the odds of kidney stones. We aimed to investigate the relationship between DEET exposure and the prevalence of kidney stones. Methods: We included 7567 qualified participants in our research from the 2007-2016 NHANES survey. We carried out three logistic regression models to explore the potential association between DEET exposure and the odds of kidney stones. Spline smoothing with generalized additive models (GAM) was utilized to assess the non-linear relationship and restricted cubic spline (RCS) curves was to determine the dose-response association. Multivariate regression models were used to conduct stratified analysis and sensitivity analysis.Results: Baseline characteristics of study participants presented the distribution of covariables. Regression analysis revealed that the odds of kidney stones were positively associated with the main metabolites of 3-diethyl-carbamoyl benzoic acid (DCBA) (log2) (OR = 1.05, 95% CI 1.02 to 1.08). The fourth quartile of urine DCBA showed a greater risk of kidney stones in the fully adjusted model (OR = 1.36, 95% CI 1.08 to 1.72). Another DEET metabolite of N, N-diethyl-3hydroxymethylbenzamide (DHMB) was used to confirm the accuracy and stability of the results. The spline smoothing curve represented two main DEET metabolites had similar no-linear relationships and a positive trend with kidney stones proportion. RCS implied that the incidence of kidney stones rose with increasing levels of DEET exposure. High-risk groups on kidney stones were exhibited by stratified analysis under DEET exposure.Conclusion: Our study suggests that DEET exposure is positively associated with odds of kidney stones. Further investigation into the underlying processes of this association is required to guide the prevention and treatment of kidney stones..